MODELING THE DEVELOPMENT OF INFORMATION SYSTEMS IN THE ECONOMY - PUSHKAR, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article addresses the issues of modeling the development of information systems in the economy. Its aim is to analyze, systematize, and generalize the existing theoretical and methodological foundations for modeling this development.The study substantiates that information systems are the foundation of the modern digital economy, as they provide the processing and analysis of data critical for decision-making. The stages of the formation of the information economy, starting from the mid-20th century, and the key aspects of its development that shaped the current approaches to modeling information systems are outlined. It is identified that at each stage of the development of the information economy, the role of information in economic processes has changed, which has become the basis for the development of information systems and the information economy as an independent field of study. An analysis of literature sources allowed for identifying four main approaches to modeling information systems development: structural, process-based, simulation, and artificial intelligence-based modeling. Each approach has its specifics and application area, enabling the resolution of various tasks in managing, optimizing, and developing information systems. Structural modeling contributes to building efficient system architecture, process-based modeling helps optimize business processes, and simulation modeling allows forecasting the outcomes of management decisions. The significance of artificial intelligence and big data in modeling is explored, as these technologies enable decision-making automation and improve forecasting accuracy. The use of technologies such as cloud computing and the Internet of Things allows for the creation of intelligent digital ecosystems, which enhance the efficiency of economic activity and the well-being of society. Overall, the study shows that modeling the development of information systems is a key factor in ensuring the adaptability and efficiency of modern economic structures. Specifically, the comprehensive application of approaches to modeling information systems allows for significant results in resource optimization, adaptation to changes, risk forecasting, and developing new technologies.
Keywords: modeling; development; information system; development of information systems; information economy; digital transformation; adaptation